Microbiological surveillance of hospital environment in tertiary care hospital in north India - Naik, Saboor; Dar, Mohammad Abass; Khan, Sufhia; Razdhan, Kanika (International Journal Of Community Medicine And Public Health, 2022)
Background: Hospital acquired infection (nosocomial infection) are commonly occurring in developing as well as developed countries almost 50% of patients in developed countries and 75% in developing countries get infected inside the hospital to which they are not exposed earlier. The problem occurring in treatment to these patients is the resistance to certain antibiotics among these bacteria. Methods: A swab soaked in nutrient broth was used to collect samples from the floor, walls, equipments, instruments, operation tables, etc. All the samples were labelled properly and immediately transported to the microbiology laboratory in Government medical college Jammu for processing. Results: Out of 29 air samples positive is 9 and the percent is 31.0 swabs are 92. Out of 92 samples positive is 28 and the percent is 30.43. Out of 29 samples 3 samples are taken from orthopaedic OT there is no growth. 3 samples are taken from gynaecology OT no growth. 4 samples are taken from urology theatre 2 are Staphylococcus aureus and the percent is 50. 2 samples are taken from eye OT there is no growth. Conclusions: These findings demonstrate that the microbiological quality of air and surfaces in operation theatre may be considered a mirror image of the hygienic conditions of the operating theatre.